TJNPR 2021
DOI: 10.26538/tjnpr/v5i6.21
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potentials of Alstonia boonei Extracts on Biochemical Markers of Brain Integrity in Experimental Rats

Abstract: The brain is a complex and extremely important part of the body. It functions through neurons and neuroglia, sending out as well as receiving and interpreting simple and complex signals in the body. 1 Neurons can be injured in the course of action through various physiological mechanisms. When this happens, Acute signals are sent to the neuroglia which has the capacity and function of destroying the or repairing the injured neurons. This action represents physiological neuroprotective response by the neuroglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…boonei has been widely used in the terrestrial animals for the treatment of various diseases due to the presence of bioactive components in all parts of the plant. Studies have shown that the plant has antiin ammatory, anti-venom, anti-poison and antimicrobial properties and a potent compound in the treatment of ulcers which is commonly found in aeromonas infection (Akinmoladun et al, 2007;Ogueke et al, 2014;Ikechukwu et al, 2021). In the same vein, M. scaber also contains bioactive ingredients that are used as therapeutic agents and feed additives.…”
Section: Introductionmentioning
confidence: 99%
“…boonei has been widely used in the terrestrial animals for the treatment of various diseases due to the presence of bioactive components in all parts of the plant. Studies have shown that the plant has antiin ammatory, anti-venom, anti-poison and antimicrobial properties and a potent compound in the treatment of ulcers which is commonly found in aeromonas infection (Akinmoladun et al, 2007;Ogueke et al, 2014;Ikechukwu et al, 2021). In the same vein, M. scaber also contains bioactive ingredients that are used as therapeutic agents and feed additives.…”
Section: Introductionmentioning
confidence: 99%